Grammatical issues in the Holy Qur'an about human creation = Isu-isu gramatikal dalam al-Qur'an tentang penciptaan manusia - Akzam, Ismail; Yaacob, Solehah@Nik Najah Fadilah (Fakultas Agama Islam, Universitas Islam Riau, 2024)
Penelitian ini berfokus pada analisis isu-isu gramatikal bahasa Arab dalam Al-Qur'an terkait penciptaan manusia, dengan mengeksplorasi interpretasi dari empat kitab tafsir utama (al-Kasysyaf Zamaksyari, al-Bahr al-Muhith Abu Hayyan al-Andalusy, Tafsir al-Qur’an al-‘Azhim Ibnu Katsir, Ruhul Ma’ani al-Alusy) dan membandingkannya dengan temuan ilmiah modern. Melalui metode analisis linguistik, analisis tafsir, serta pendekatan interdisipliner yang menggabungkan prinsip-prinsip teologi, linguistik, dan ilmu pengetahuan, penelitian ini bertujuan untuk mengungkap kesesuaian dan perbedaan antara narasi Al-Qur'an dan pemahaman ilmiah tentang penciptaan manusia. Temuan utama menunjukkan adanya kesesuaian dan perbedaan signifikan, serta menyoroti keragaman interpretasi dalam tafsir. Penelitian ini menggarisbawahi pentingnya pendekatan interdisipliner dalam memahami teks-teks agama, memberikan kontribusi yang signifikan terhadap pemahaman tentang penciptaan manusia. ________ This research focuses on the analysis of grammatical issues in the Arabic language within the Qur'an, specifically related to the creation of humans. It explores the interpretations from four major exegesis books (al-Kashaf by Zamakhshari, al-Bahr al-Muhit by Abu Hayyan al-Andalusi, Tafsir al-Qur'an al-'Azhim by Ibn Kathir, Ruhul Ma'ani by Al-Alusi) and compares them with modern scientific findings. Through linguistic analysis, tafsir analysis, and an interdisciplinary approach that combines theological principles, linguistics, and scientific knowledge, this research aims to uncover the similarities and differences between the narratives in the Qur'an and the scientific understanding of human creation. The main findings indicate both significant similarities and differences, highlighting the diversity of interpretations within the exegesis. This research underscores the importance of an interdisciplinary approach in understanding religious texts and contributes significantly to the understanding of human creation.